Mapping Of Pulmonary Disease Ontology Terms Using Graph Stream - Radhika, P; Verma, P. Suresh; Kalyani, N. Lakshmi; Krishna, P. Rama (International Journal of Computer Sciences and Engineering, 2025)
Since long, organizations have been looking for information sources that can store data which can provide structured organization and focuses on meaning access of data. Sematic web helps a lot in this context to retrieve meaningful data. This paper emphasizes on mapping developed ontology terms and their retrieval with the help of Graph Stream. We developed an ontology for Pulmonary diseases which consists of classes , objects, relations, and their properties and division of diseases is given as sub classes and Levenshtein’s Edit system algorithm has been used for similarity calculations. The generated ontology has been sent for preprocessing and is fed to Graph Stream for graph generation. The results produced are comparable to the results of human annotators